2021
DOI: 10.1021/acs.molpharmaceut.0c00948
|View full text |Cite
|
Sign up to set email alerts
|

Linking In Vitro Intrinsic Dissolution Rate and Thermodynamic Solubility with Pharmacokinetic Profiles of Bedaquiline Long-Acting Aqueous Microsuspensions in Rats

Abstract: Pharmacokinetic (PK) profiles of a range of bedaquiline (BDQ) long-acting injectable (LAI) microsuspensions in rats after parenteral (i.e., intramuscular and subcutaneous) administration were correlated with the in vitro intrinsic dissolution rate (IDR) and thermodynamic solubility of BDQ in media varying in surfactant type and concentration to better understand the impact of different nonionic surfactants on the in vivo performance of BDQ LAI microsuspensions. All LAI formulations had a similar particle size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…As mentioned above, drug substance precipitation, redissolution, and/or diffusion are likely the driving factors for drug release from the bedaquiline ISGs rather than polymer erosion. The fact that the PK profiles resemble those obtained for 200 mg eq./g bedaquiline microsuspensions administered SC to rats supports this thinking [ 7 ]. The microsuspensions were prepared with crystalline bedaquiline (free form), while X-ray diffraction (XRD), DSC, and IR analysis of spherical ISGs formed from formulations 1 and 2 in 0.05 M phosphate buffer at pH 7.4 or in water confirmed the presence of amorphous bedaquiline free form and/or salt.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…As mentioned above, drug substance precipitation, redissolution, and/or diffusion are likely the driving factors for drug release from the bedaquiline ISGs rather than polymer erosion. The fact that the PK profiles resemble those obtained for 200 mg eq./g bedaquiline microsuspensions administered SC to rats supports this thinking [ 7 ]. The microsuspensions were prepared with crystalline bedaquiline (free form), while X-ray diffraction (XRD), DSC, and IR analysis of spherical ISGs formed from formulations 1 and 2 in 0.05 M phosphate buffer at pH 7.4 or in water confirmed the presence of amorphous bedaquiline free form and/or salt.…”
Section: Discussionmentioning
confidence: 64%
“…Recent studies have demonstrated favourable pharmacokinetic profiles and antiviral activity after intramuscular or subcutaneous injection of bedaquiline LAI microsuspensions in rodents [ 6 , 7 ]. The high lipophilicity (log P 7.3), low aqueous solubility (<0.005 mg/mL at pH 7.4), and high potency against M. tuberculosis (minimal inhibitory concentration of 0.03 µg/mL) make bedaquiline a suitable candidate for this type of LAI formulation [ 6 , 7 ]. However, LAI microsuspensions have some disadvantages: for example, their complex and costly manufacturing process and physical stability challenges related to particle size growth.…”
Section: Introductionmentioning
confidence: 99%
“…It has high lipophilicity (logP, 7.3), and a long half-life (about 24 h, functionally or effectively) which makes it suitable for use in an LAI formulation [21]. The efficacy of LAI BDQ has been already demonstrated in a latent tuberculosis infection mouse model [21][22][23]. Due to the very slow doubling time of M. leprae, a unique administration of LAI BDQ could also be considered.…”
Section: Competing Interestsmentioning
confidence: 99%
“…It has high lipophilicity (logP, 7.3), and a long half-life (about 24 h, functionally or effectively) which makes it suitable for use in an LAI formulation [21]. The efficacy of LAI BDQ has been already demonstrated in a latent tuberculosis infection mouse model [21][22][23]. Due to the very slow doubling time of M. leprae, a unique administration of standard of LAI BDQ could also be considered.…”
Section: Introductionmentioning
confidence: 99%